A framework for adapting to climate change risk in coastal cities. (3rd April 2017) - Wallace, Ben
ABSTRACT: Disaster management practitioners are accustomed to dealing with changing climates, but rapid anthropogenic climate change is an unprecedented problem. Hazards (e.g. storms, coastal flooding, sea level rise, heat waves) combine with vulnerabilities (e.g. socioeconomic disparity, rapid urbanization, improper land use, rigid governance structures) to increase disaster risk in some coastal cities. Focus on climate change adaptation (CCA) has been increasing as part of the answer to this problem. However, CCA has regularly developed separately from relatively established disaster management efforts, and this paper argues that CCA should generally be included as part of disaster management efforts, utilizing extant social structures, funding streams, theories, and more to avoid duplication of effort. Building on this conceptual foundation, the paper presents a framework for guiding and assessing efforts to reduce this risk. The framework was based on theory, then modified during a case study of New York City. This allowed refinement based on real-world planning, resulting in a theoretically grounded framework with a strong focus on application. Key points from the investigation are summarized here, interesting themes are discussed, and notes on applying the framework are presented.